Penguatan Literasi Digital Marketing bagi Pelaku UMKM Desa Klambir Lima Kebun Kecamatan Hamparan Perak - Hidayati Purnama Lubis; Rahayu Mayang Sari; Riska Franita (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This community service activity aims to improve the capacity and strengthen the digital literacy of Micro, Small, and Medium Enterprises (MSMEs) in Klambir Lima Kebun Village, Hamparan Perak District, in utilizing digital technology as a means of marketing their products. The main problems faced by MSME players in this village are a low understanding of digital marketing strategies, limited effective use of social media, and a lack of ability to manage digital content that is attractive and suitable for the target market. Through this community service activity, participants were equipped with basic knowledge and digital literacy, digital marketing strategies, the use of e-commerce platforms, and techniques for creating photo and video-based promotional content. The implementation methods included socialization, practical training, and mentoring for community service participants. The results of the activity showed an increase in the understanding and skills of MSME actors in managing digital business accounts and utilizing social media such as Instagram, Facebook, and WhatsApp Business as effective marketing tools. With this activity, it is hoped that MSME actors in Klambir Lima Kebun Village will be able to expand their market reach, increase sales, and adapt to the development of the digital economy in a sustainable manner.